Antinociceptive Action of Icon®, a Pyrethroid Insecticide on Pregnant Rats - Ratnasooriya, W.D.; Ratnayake, S.S.K.; Jayatunga, Y.N.A. (My University, 2002)
Icon® is a type II synthetic pyrethroid insecticide based on active ingredient Lambda cyhalothrin (10% w/w). In a recent study it was evident that this insecticide although induced marked signs of stress and other overt signs of toxicity in pregnant rats it never provoked aversive behaviours: suggestive of antinociceptive activity. Hence this study was conducted to investigate the possible antinociceptive potential of leon® on pregnant rats. Different doses ofIcon® 0, 63,83 or 125 mg/ kg body weight/day (active ingredient 0,6.3,8.3, 12.5 mg / kg body weight/day) was orally administered to pregnant (early, mid and late) rats for seven consecutive days and antinociception potential was determined using the hot plate technique. The results showed a marked antinocicpetive activity (in terms of prolongation of reaction time) of leon in pregnant rats. It is concluded that the antinociception is mediated by both specific (neuronal) and non specific (stress and food inhibition) mechanisms.
Keywords: Antinociception; Icon®; Lambda-cyhalothrine; Insecticide; Pyrethroid; Pregnancy